2003
DOI: 10.1074/jbc.m307289200
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Activators Control Splicing and 3′-End Cleavage Levels

Abstract: We have investigated whether transcriptional activators influence the efficiency of constitutive splicing and 3 -end formation, in addition to transcription levels. Remarkably, strong activators result in higher levels of splicing and 3 -cleavage than weak activators and can control the efficiency of these steps in pre-mRNA processing separately. The pre-mRNA processing stimulatory property of activators is dependent on their binding to promoters, but is not an indirect consequence of the levels of transcripts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 45 publications
(50 reference statements)
1
58
0
Order By: Relevance
“…Recruitment of several different transcriptional activators to a promoter controls the splicing efficiency of a constitutively spliced Drosophila doublesex intron; strong activators induce higher levels of splicing than weak activators (3). This result is not merely an indirect effect of the relative concentration of splicing precursors since the efficiency of splicing does not correlate with the level of transcripts (3).…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Recruitment of several different transcriptional activators to a promoter controls the splicing efficiency of a constitutively spliced Drosophila doublesex intron; strong activators induce higher levels of splicing than weak activators (3). This result is not merely an indirect effect of the relative concentration of splicing precursors since the efficiency of splicing does not correlate with the level of transcripts (3).…”
mentioning
confidence: 76%
“…The MAZ4 Effect Is Promoter-dependent-Alternative splicing decisions have previously been shown to be dependent upon transcription by altering promoter structure (3)(4)(5)(6)(7)(8). To confirm that the MAZ4 effect on splicing was dependent on transcription, the FGFR2 wild-type minigene and insertion constructs were cloned downstream of the adenovirus major late (ADML) promoter.…”
Section: Construction Of Co-transcriptional Splicing Reportermentioning
confidence: 99%
“…Recognition of the 3Ј-terminal exons has been postulated to involve an interaction of splicing and polyadenylation factors, and a growing number of reports support this view (42)(43)(44)(45)(46)(47)(48)(49)(50). Because the RS domain of SR proteins mediates protein-protein interactions that are important for spliceosome assembly The cells were fixed and immunostained with antibodies against nuclear markers (red).…”
Section: Cf I M 68 Interacts With the 25-kda Protein Via Its Rrm-mentioning
confidence: 99%
“…In a subsequent study by the same investigators, it was demonstrated that factors influencing pol II processivity, including transcriptional activators, influence EDI inclusion levels, apparently by enhancing or delaying the transcription of cis-acting splicing-regulatory sequences that modulate the selection of adjacent splice sites . We recently showed that strong transcriptional activators can result in the increased pre-mRNA splicing of constitutive introns, as well as increased cleavage levels (Rosonina et al 2003). These effects of strong activators were shown to be dependent on the pol II CTD.…”
Section: Introductionmentioning
confidence: 99%